2011
DOI: 10.1007/s00709-011-0292-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hexavalent chromium on microtubule organization, ER distribution and callose deposition in root tip cells of Allium cepa L.

Abstract: The subcellular targets of hexavalent chromium [Cr(VI)] were examined in Allium cepa root tips with confocal laser scanning microscopy. Cr(VI) exerted dose- and time-dependent negative effects on root growth rate, the mitotic index and microtubule (MT) organization during cell division cycle. Interphase MTs were more resistant than the mitotic ones, but when affected they were shorter, sparse and disoriented. The preprophase band of MTs became poorly organized, branched or with fragmented MTs, whilst neither a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 58 publications
(87 reference statements)
5
37
0
Order By: Relevance
“…Increase in number of nuclei and vacuolar size and its number as well as the presence of Cr dense precipitates in the dead parts of the cell in all these cultivars shows a positive indication that they can be used for phytoremediation purpose in Cr-contaminated areas. Consistent with our results, Panda [22] in rice seedlings, Speranza et al [50] in the pollen grains of kiwi, and Eleftheriou et al [51] in Allium cepa observed almost similar ultramorphological features in Cr-treated root samples.…”
Section: Discussionsupporting
confidence: 92%
“…Increase in number of nuclei and vacuolar size and its number as well as the presence of Cr dense precipitates in the dead parts of the cell in all these cultivars shows a positive indication that they can be used for phytoremediation purpose in Cr-contaminated areas. Consistent with our results, Panda [22] in rice seedlings, Speranza et al [50] in the pollen grains of kiwi, and Eleftheriou et al [51] in Allium cepa observed almost similar ultramorphological features in Cr-treated root samples.…”
Section: Discussionsupporting
confidence: 92%
“…MT effect is a less explored parameter (Fusconi et al 2007). In the present study, we show that MTs of five Fabaceae species constitute a prime subcellular target of Cr(VI) toxicity, thus substantiating the notion that MTs could be a universal target of Cr(VI) toxicity (Eleftheriou et al 2012. The universality of MT targeting by tungsten, another heavy metal belonging to the same group (VI-B) of the periodic table of elements along with Cr, was shown in taxonomically diverse land plant taxa representing monocots, dicots, gymnosperms, pterophytes, and bryophytes (Adamakis et al 2010b).…”
Section: Universality Of Microtubule Disruption By Cr(vi)supporting
confidence: 77%
“…More recently, differential effects of Cr(VI) in two unrelated plant species were reported. In A. cepa, cortical MTs were extensively fragmented and depolymerized (Eleftheriou et al 2012). Similarly, cortical MTs of V. faba herewith examined were depolymerized and disappeared after prolonged treatment with Cr(VI).…”
Section: Universality Of Microtubule Disruption By Cr(vi)mentioning
confidence: 85%
See 1 more Smart Citation
“…Several studies have shown that microtubules are very sensitive to stress conditions and that the array and synthesis of microtubules can be influenced by temperature, drugs, or metal ions [9,32]. Several studies have shown that microtubules are very sensitive to stress conditions and that the array and synthesis of microtubules can be influenced by temperature, drugs, or metal ions [9,32].…”
Section: Discussionmentioning
confidence: 99%